Morse Alphabet and Numbers - Ward, Lock (Wonders of electricity and the elements, being a popular account of modern electrical and magnetic discoveries, magnetism and electric machines, the electric telegraph and the electric light, and the metal bases, salt, and acids, 1870)
Text and table detailing the Morse code alphabet and numerals used to communicate via telegraph.
Keywords: Telegraph; Telecommunication; Morse code; Communication; Communication and technology; Cipher and telegraph codes